Apoplastic Extracts from a Transgenic Wheat Line Exhibiting Lesion-Mimic Phenotype Have Multiple Pathogenesis-Related Proteins That Are Antifungal - Ajith Anand; Zhentian Lei; Lloyd W. Sumner; Kirankumar S. Mysore; Yasuyuki Arakane; William W. Bockus; Subbaratnam Muthukrishnan (Molecular Plant-Microbe Interactions, 2004)
A transgenic wheat line constitutively expressing genes encoding a class IV acidic chitinase and an acidic β-1,3-glucanase, showed significant delay in spread of Fusarium head blight (scab) disease under greenhouse conditions. In an earlier work, we observed a lesion-mimic phenotype in this transgenic line when homozygous for transgene loci. Apoplastic fluid (AF) extracted from the lesion-mimic plants had pathogenesis-related (PR) proteins belonging to families of β-1,3-glucanases, chitinases, and thaumatin-like proteins (TLPs). AF had growth inhibitory activity against certain fungal pathogens, including Fusarium graminearum and Gaeumannomyces graminis var. tritici. Through a two-step ion-exchange chromatography protocol, we recovered many PR proteins and a few uncharacterized proteins. Three individual protein bands corresponding to a TLP (molecular mass, 16 kDa) and two β-1,3-glucanases (molecular mass, 32 kDa each) were purified and identified by tandem mass spectrometry. We measured the in vitro antifungal activity of the three purified enzymes and a barley class II chitinase (purified earlier in our laboratory) in microtiter plate assays with macroconidia or conidiophores of F. graminearum and Pyrenophora tritici-repentis. Mixtures of proteins revealed synergistic or additive inhibitory activity against F. graminearum and P. tritici-repentis hyphae. The concentrations of PR proteins at which these effects were observed are likely to be those reached in AF of cells exhibiting a hypersensitive response. Our results suggest that apoplastic PR proteins are antifungal and their antimicrobial potency is dependent on concentrations and combinations that are effectively reached in plants following microbial attack.